SP5.2.4 Stent-graft endobypass for non-infected femoral pseudoaneurysms in high-risk surgical patients: acceptable short-to-mid-term results. (28th October 2021) - Chaudhuri, Arindam; Dey, Ramita; Stupalkowska, Weronika
Abstract: Aim: Stent-grafts are finding a place in the treatment of femoral pseudoaneurysms (FpsAs), having been described in the treatment of infected pseudoaneurysms. We present the results of endovascular treatment of non-infected FpsAs using stent-grafts. Methods: Case series of patients who underwent stent-graft coverage of FpsAs from January 2016 to December 2020. Stent-graft fractures, occlusions and reinterventions, length of stay (LOS) and 30-day mortality were assessed. Results: 11 patients (mean age 75±10.3 years, 7 males; all ASA 3 or 4) underwent stent-graft coverage of FpsAs. Original procedures linked to the formation of FpsA were iliofemoral bypass (n = 3), femorofemoral crossover (n = 3), percutaneous coronary interventions (n = 2), aortobifemoral bypass (n = 1), endovascular aneurysm repair (n = 1) and femoral endarterectomy (n = 1). 3 patients had previous open FpsA repair. Technical success of deployment was 100%. Stent-grafts used included Viabahn Endoprosthesis (WL Gore & Associates, Flagstaff USA; n = 8), Viabahn VBX (WL Gore & Associates; n = 1) and BeGraft (Bentley InnoMed GmbH, Hechingen, Germany; n = 2). All patients were maintained on either antiplatelets or anticoagulant. 10 patients were available for analysis (1 lost to follow-up); radiological follow-up included initial computed tomography angiography and later combined duplex ultrasonography/plain radiography. Median LOS was 4 days (IQR 4). 30-day mortality was 0%. Median survival was 12 months (IQR 17). There was one stent-graft occlusion requiring thrombectomy but no fractures were observed in this series. Conclusions: This small series suggests that there may be a role for stent-grafts in treatment of FpsAs in carefully selected patients. Given lack of data on long-term outcomes, continued surveillance is recommended.